Kompleksitas Tokoh Pandita Drona dalam Artefak Wayang Kulit Cirebon - Moh. Isa Pramana Koesoemadinata (PANGGUNG, 2012)
Since early centuries of Christian calendar, the Indian epics Mahabharata and Ramayana have widely spread across the Nusantara Archipelago.  By the time these epics arrived here, they were not presented in their genuine forms, but had been adopted and localized in order to approach the natives.  The adaptation process included taking the shadow theatrical form, translating and interpretating the stories, and transforming character and visual descriptions which were manifested into puppet form.            One of the character transformations which includes personality and visual descriptions was done to Priest Drona, the vital character roled as guru to both Pandawas and Kurawas, who was trapped inside the dilemma among his disciples.  In Javanese version, Drona has been transformed into an ambiguous, mischievous, and slightly humorous character.  In Cirebon version, Drona was depicted as an evil character who provoked the Battle of Bharata yuddha.  Drona puppet himself has unique and specific visual attributes compared to other puppet main characters, and each form of puppet Drona possess a high symbolic meaning beneath them.  The problem is how do the visual attributes of each puppet tell us about the character’s complexity? This paper analyzes every visual variation of Drona leather puppet in Cirebon using the Art Criticism methods and semiotics referring to general Javanese Shadow Puppetry performance.  This analysis proves the complexity of the character based on the differences of cloth, accessories and other visual attributes from Cirebon perspective. Keywords: Cirebonese leather puppets, character, Drona, visual attributes